FA01.04: HIGH HOSPITAL VOLUME IS ASSOCIATED WITH SHORTER LEARNING CURVES AND LESS LEARNING ASSOCIATED MORBIDITY AFTER MINIMALLY INVASIVE ESOPHAGECTOMY. (14th September 2018) - Workum, Frans; Claassens, Linda; Rovers, Maroeska; Rosman, Camiel
Abstract: Background: Ivor Lewis totally minimally invasive esophagectomy (TMIE) is associated with a long learning curve and high learning associated morbidity. Factors that are associated with a shorter learning curve and less associated morbidity have not been investigated from clinical data. The aim of this study was to investigate whether there is a relationship between hospital volume and the length of the learning curve and learning associated morbidity. Methods: Prospectively collected data were retrospectively analyzed of all consecutive patients undergoing Ivor Lewis TMIE in expert centers in Sweden, Denmark and the Netherlands. The primary outcome parameter was anastomotic leakage requiring reoperation or reintervention. Learning curves were plotted using weighted moving average and CUSUM analysis was used to determine after how many cases the plateau was reached. Learning associated morbidity was calculated with area under the curve analysis. The length of the learning curve and learning associated morbidity were compared between hospitals < 50 procedures per year (normal volume) and hospitals performing > 50 procedures (high volume) per year. Results: Nine centers participated and 906 patients were included. The mean number of Ivor Lewis TMIE performed per center per year was 41 (range 22–60). The overall length of the learning curve was 136 cases and this was 148 cases in the normal volume group versus 122 cases in the high volume group. Learning associated anastomotic leakage occurred in 10 patients (7.4% of all patients operated during the learning curve) and this was 13 patients (8.5%) in the normal volume group versus 6 patients (5.2%) in the high volume group. Conclusion: Learning curves were shorter and learning associated morbidity was lower in centers with higher case volume. This is the first study demonstrating this effect from clinical data. Patient safety can be significantly compromised during surgical learning curves and probably, patient safety can be increased if surgeons learn technically challenging procedures in higher volume centers. Our data can guide the design of implementation programs for technically challenging procedures. This abstract was submitted on behalf of the esophagectomy learning curve collaborative group. Disclosure: All authors have declared no conflicts of interest.